APPLICATION OF THE EDUCATIONAL INFORMATION SYSTEMS IN PROFESSIONAL TRAINING OF AGRICULTURAL ENGINEERS STUDYING PHYSICS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article deals with application of educational information systems in professional training of agricultural engineers studying physics with an emphasis on practice-oriented teaching methods. Physics is a key discipline that ensures the formation of engineering competencies that are necessary for solving problems of an agro-industrial complex. The modern digital technologies make it possible to significantly improve the quality of education, making the learning process more interactive, visual and closer to real professional activity. Particular attention is paid to application of practice-oriented methods, such as professional tests, case methods and digital simulators. Professional tests allow the students to simulate real engineering activities by solving practical problems, related to physical processes in agricultural engineering. The case method promotes the development of analytical and critical thinking, offering the students an opportunity to analyse real situations and engineering problems, followed by a search for optimal solutions. Application of digital simulators makes it possible to model complex physical phenomena and technological processes, conduct virtual experiments and analyse the results, which is especially important in conditions of a limited access to the laboratory equipment. There is an analysis made of the integration efficiency of the educational information systems into the educational process. The obtained results show that the use of these technologies helps to increase the level of mastering the educational material by 20–30%; it increases the degree of the students’ involvement in the educational process and improves the indicators of independent work. In addition, the students develop practical skills, related to the analysis of the engineering problems and the use of digital tools. A conclusion is made that application of practice-oriented methods in combination with the possibilities of the educational information systems allows not only to improve the quality of studying physics but also to create conditions for the development of the students’ engineering thinking, the skills to work with digital tools and competencies, necessary for efficient operation in a modern agro-industrial complex